White guilt and racial imagery in Annette K. Olesen's Little Soldier. Issue 2 (2nd April 2018) - Oxfeldt, Elisabeth
ABSTRACT: The article analyzes Annette K. Olesen's Little Soldier (Lille Soldat, 2008), from the perspective of "white guilt" (or the "white man's burden") as it is thematized in the film. It furthermore critiques the film's portrayal of the two female protagonists, Lotte and Lily, as racialized opposites. This is done from the perspective of postfeminism and critical race and whiteness studies. The readings include an evaluation of the film as a globalized, postfeminist version of Martin Scorcese's Taxi Driver as well as an interpretation of the film as a national allegory. Overall, I argue that while the film contains many pertinent, well-chosen images and symbols of a destructive form of white guilt, it is ultimately based on two female figures whose opposite character traits come across as founded on, and thus also as perpetuating, stereotypical racial imagery.